Rack1 promotes breast cancer stemness properties and tumorigenesis through the E2F1-SOX2 axis - Yidi Jia; Luoming Zhang; Wei Zhou; Shuhua Chen; He Zhang; Liming Liu; Hui Guo; Zhiyong Wang; Yanfen Cui; Ruifang Niu; Fei Zhang (Cancer Cell International)
Abstract Background Breast cancer remains the most prevalent malignancy and the leading cause of cancer-related mortality among women worldwide. The primary factors contributing to the deterioration and death of patients with breast cancer are metastasis, recurrence, and drug resistance. These phenomena are closely related to the presence of breast cancer stem cells; however, the exact mechanisms regulating stemness remain to be elucidated. Rack1 (Receptor for Activated C Kinase 1), a well-known versatile scaffold protein, has been implicated in tumorigenesis and progression in numerous cancer types; however, its specific role in breast cancer stemness remains to be elucidated. Methods Using bioinformatic and immunohistochemical approaches, we validated that the expression level of Rack1 is associated with cancer stemness and affects the prognosis of patients. Through a series of experimental methods including mammosphere formation assay, flow cytometry, qPCR, Western blotting, and CHX assays, we validated at the molecular and cellular levels the mechanism by which Rack1 influences cancer stemness via the E2F1/SOX2 axis. Furthermore, by designing and utilizing lentiviral constructs to establish xenograft tumor models in mice, we further confirmed in vivo the impact of the Rack1/E2F1/SOX2 axis on the tumorigenic capacity of breast cancer cells. Results Our findings indicate that Rack1 plays a critical role in preserving the stemness characteristics of breast cancer cells. Mechanistically, the observed effects of Rack1 are achieved through the modulation of SOX2 expression, a master transcription factor that regulates cancer cell stemness and maintenance. We further demonstrate that Rack1 increases the stability of the E2F1 protein by inhibiting its ubiquitination and subsequent proteasome-mediated degradation, which in turn transcriptionally upregulates SOX2, thereby maintaining breast cancer cell stemness and tumorigenesis. Conclusion This study thus unveils a novel mechanism through which Rack1 executes its oncogenic function. This study also demonstrates that targeting the Rack1-E2F-SOX2 axis may be a potential strategy to inhibit breast cancer development and progression.